AN ASSESSMENT OF THE TRAINING AND SERVICES OF COMMUNITY-BASED DISTRIBUTION (CBD) WORKERS IN OYO STATE (1985)
The study attempted to assess the effectiveness of the Community Based Distribution (CBD) programme of low-cost Family Planning, Maternal and Child Health Services. This was established in 1979 by the Fertility Research Unit of the Department of Obstetric and Gynaecology, University College Hospital, Ibadan in collaboration with Oyo State Ministry of Health the Pathfinder Fund of Boston; and the Centre for Population and Family, Columbia University both in the United States of America, The C.B.D., an innovative programme, consists of the training and utilization of Traditional Birth Attendants (TBAs) and Voluntary Health Workers (VHWs) to provide Primary Health Care to the door steps of the rural communities who live on the out-skirts of the main stream of sophisticated health technology. The pilot project site was Akinyele Local Government, a rural area, North of Ibadan with a population of 89,900. It was found that the programme was successful because within two years of its implementation, the population served increased from an initial 89,900 to 238,696 and the number of Zones from one to five. At the request of the Oyo State Ministry of Health officials, the project was extended to other Health Zones in Oyo State: Oyo, Oshun, Ife/ljesha Health Zones. The study assessed the training of the CBD workers with particular emphasis on the educational components of the training curriculum and also the educational activities of the CBD workers and their impact on their client community. The CBD training curriculum findings indicate that as designed presently, has enough contents which are relevant to the training objectives. However, it will be more useful, if it is developed into a standard training manual with clearly stated objectives, training methodologies and an evaluation instrument which will set an acceptable level of attainment for a trainee to qualify as a CBD worker. In relation to the application of the training, most of the CBD workers to a large extent were found to perform well on what they were taught to do - knowledge of educational tasks, performance of educational task and effectiveness of educational task. The response and support of the community members especially the clients, to the educational activities of the CBD workers was found to be positive. However, the CBD workers advocate that the government should re—introduce the monthly incentives because the CBD workers in carrying out their activities, incur tangible and intangible cost.